2020
DOI: 10.1680/jmacr.18.00541
|View full text |Cite
|
Sign up to set email alerts
|

Impact behaviour of nanomodified deflection-hardening fibre-reinforced concretes

Abstract: The behaviour of concrete under sudden impact loads is complex. Moreover, very little is known about the impact behaviour of high-performance fibre-reinforced concretes (HPFRCs). To account for this, nanomodified deflection-hardening HPFRC mixtures incorporating coarse aggregates were produced with three ratios of fly ash to Portland cement (0·0, 0·2 and 0·4), three nanomaterials (nanosilica, nano-alumina and nanocalcite) and two hybridised fibre combinations (hooked-end steel with polyvinyl alcohol, or hooked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…These matrix enhancements also led to visible scratching of the fiber's surface and a slip-hardening behavior instead of the typically observed slip-softening behavior with steel fibers [25,26]. Wu et al and Demirhan et al [27,28] observed improvement in the matrix microstructure due to the addition of nanoparticles, which led to higher pullout loads on steel fibers.…”
Section: Materials and MIX Proportionsmentioning
confidence: 98%
“…These matrix enhancements also led to visible scratching of the fiber's surface and a slip-hardening behavior instead of the typically observed slip-softening behavior with steel fibers [25,26]. Wu et al and Demirhan et al [27,28] observed improvement in the matrix microstructure due to the addition of nanoparticles, which led to higher pullout loads on steel fibers.…”
Section: Materials and MIX Proportionsmentioning
confidence: 98%
“…In normal concrete, initial microcracks are predominantly found at the interface between the cement mortar and aggregate. Upon impact, these microcracks do not have sufficient time to expand along the path of least resistance, instead, they propagate directly www.nature.com/scientificreports/ through the aggregate, resulting in macroscopic cracks 52 . Consequently, normal concrete specimens exhibit crush damage.…”
Section: Failure Modesmentioning
confidence: 99%
“…Thus, the stress-strain relationships for both compression and tension loading are obtained by formulas [3] and [4]. In these formulas, E 0 , are initial elastic stiffness of the material, equivalent plastic strain in compression and tension respectively (18).…”
Section: Numerical Analysismentioning
confidence: 99%